T-cell receptor gene rearrangement studies in Sezary syndrome - Santangelo, C... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1996)
Sezary syndrome (SS) is a cutaneous T-cell lymphoma characterized by pruritic erythroderma, generalized adenopathy and circulating Sezary cells in peripheral blood. The Sezary cells' percentage and morphology necessary for the diagnosis are still unknown; therefore, recently T-lymphocyte receptors gene rearrangement has been employed thus allowing to study the monoclonality of lymphoproliferative disorders. In order to verify the specificity and the diagnostic relevance of the above mentioned method, the DNA obtained from the peripheral blood of 17 subjects (10 affected by SS and 7 by inflammatory erythroderma) was analyzed by the Southern Blot Analysis (SBA). A monoclonal gene rearrangement of the TcR a-chain was shown in 6 subjects affected by SS. In 2 patients the analysis was repeated during the therapy with recombinant interferon alpha-2a (rIFNalpha-2a), in one patient the clonal population had disappeared. In 4 patients with CSCs and germline pattern in the peripheral blood ("false negatives") gene rearrangement bands were obtained in skin and lymphnodes except for in one patient. Seven controls with intlammatory erythroderma presented a germline pattern. These results suggest that the TcR gene rearrangement, although it is a useful diagnostic tool, must always he associated with clinical, histopathological and immunophenotypical data; Furthermore, this study highlights the need to make consecutive sampling, possibly with material from various organs (peripheral blood, lymphnodes, skin).
Keywords: Blotting, southern; Gene rearrangement, t-lymphocyte; Sezary syndrome